Rise of the legal COO. (2021) - Bull, Chris, 1966-; McKenna, Patrick J; Prescott, Blane R; Perkins, James G; Mitchell, Alastair; Harrington, Rod; Gini, Sherry; DeLargy, Michael L
No abstract available